KAJI NUMERIK DAN EKSPERIMENTAL PENYERAPAN ENERGI TABUNG ALUMINIUM BERGALUR DENGAN BEBAN AKSIAL - Hadi, Bambang K; Putra, Ichsan S; Basuki, David; Tedy S, Yanyan (Mesin, 2007)
Grooved tubes under axial compression are widely used as efficient energy absorption structures. The energy absorption uses plastic folding mechanisms that are formed during the loading. In this paper, the behaviors of grooved tubes under axial compression loading are discussed. The diameter of the tubes is 100 mm, with 2 mm thickness and the length is 72 mm. The number of grooves is 3 and 7, with the grooveâs depth is 1 mm. The study uses analytical method, numerical method using explicit dynamic of ABAQUS as well as experimental methods. The results show that increasing the number of grooves will reduce the mean crushing load, Pm. The numerical analysis is able to predict precisely the final plastic folding form of the tubes compared to the experimental results. The difference of Pm among the three methods varies between 1 â 20%. Further investigation is needed to reduce the differences. In all the studies conducted here, the mean crushing loads of the experimental data are always greater than both numerical and analytical methods.